KEANEKARAGAMAN SERANGGA DI KAWASAN IUPHHK-HTI PT. MUARA SUNGAI LANDAK KABUPATEN MEMPAWAH KALIMANTAN BARAT - Ricco, Fredicus; Kustiati, Kustiati; Riyandi, Riyandi (Universitas Tanjungpura, 2019)
Insect is a dominant group of animals on earth with the most common number of species and individuals compared to other animal groups. Research about insect diversity in the forest area of IUPHHK-HTI PT. Muara Sungai Landak in swamp peat forest should be done to know its role. The research was aimed to determine the species of insects and to know the effect of environmental factors to insects in the area of PT. Muara Sungai Landak. Insects collected from five different age groups of plants with trapping methods using pit fall trap, yellow pan trap, and light trap. Insects found in the area of PT. Muara Sungai Landak counted as many as to 282 individuals consisting of 18 species, 15 families, and 6 orders. The most widely found number of individuals was the species of Condylostylus longicornis. The highest diversity value was found in the two-year plant age group with a diversity value of H' = 1,69654, while the lowest diversity value was found in the three-year plant age group with the value H ' = 1,20751